Thermally conductive sheet

A resin composition with triphenylmethane type epoxy resin and phenolic resin improves thermal conductivity and dielectric properties by enhancing crosslinking and reducing phonon scattering, addressing the insufficiency of existing compositions.

JP7606312B2Active Publication Date: 2024-12-25NITTO SHINKO KK
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2020168670
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-05
Publication Date
2024-12-25
Estimated Expiration
2040-10-05

AI Technical Summary

Technical Problem

Existing resin compositions containing epoxy resin, curing agent, and inorganic filler do not exhibit sufficient thermal conductivity when cured.

Method used

A resin composition comprising a triphenylmethane type epoxy resin and a triphenylmethane type phenolic resin as curing agent, with inorganic filler dispersed in the epoxy resin, enhances thermal conductivity by promoting crosslinking and reducing phonon scattering.

Benefits of technology

The resin composition achieves significant improvement in thermal conductivity, peel strength, and dielectric properties of the cured product, making it suitable for applications in circuit boards and power modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606312000024
    Figure 0007606312000024
  • Figure 0007606312000025
    Figure 0007606312000025
  • Figure 0007606312000001
    Figure 0007606312000001
Patent Text Reader

Abstract

To provide a resin composition or the like that can exhibit sufficient heat conductivity when it becomes a cured product.SOLUTION: A resin composition according to the present invention contains an epoxy resin, a curing agent, and an inorganic filler, wherein the inorganic filler is dispersed in the epoxy resin, the epoxy resin contains a particular polyfunctional epoxy resin, and the curing agent contains a particular polyfunctional phenol resin.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a thermally conductive sheet. [Background technology]

[0002] 2. Description of the Related Art Conventionally, in the field of electronics, a resin composition containing an epoxy resin, a curing agent, and an inorganic filler has been used.

[0003] Patent Document 1 listed below discloses that a resin composition containing an epoxy resin, a curing agent, and an inorganic filler is cured and used as a heat dissipation sheet. Such a heat dissipating sheet has heat dissipation properties because it contains a relatively large amount of inorganic filler such as boron nitride filler. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2010-94887 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, although the resin composition described in Patent Document 1 contains a relatively large amount of inorganic filler as described above, there is a problem in that the thermal conductivity (heat dissipation property) of the cured product is not necessarily sufficient.

[0006] Therefore, an object of the present invention is to provide a resin composition that can exhibit sufficient thermal conductivity when cured, and a thermally conductive sheet having a resin layer composed of the resin composition. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted extensive research and have found that in a resin composition containing an epoxy resin, a curing agent, and an inorganic filler, in which the inorganic filler is dispersed in the epoxy resin, by using a specific epoxy resin and a specific curing agent, the thermal conductivity of the cured product becomes sufficiently high when the product is cured, and have arrived at the present invention.

[0008] That is, the resin composition according to the present invention is a resin composition containing an epoxy resin, a curing agent, and an inorganic filler, the inorganic filler being dispersed in the epoxy resin, The epoxy resin contains a triphenylmethane type epoxy resin represented by the following formula (1): The curing agent contains at least one of triphenylmethane type phenolic resins represented by the following formula (2) or (3).

[0009] [ka] (In formula (1), R is C n H 2n+1 where n is an integer equal to or greater than 0.

[0010] [ka] (In formula (2), R is C n H 2n+1 where n is an integer equal to or greater than 0.

[0011] [ka] (In formula (3), n is an integer between 1 and 20.)

[0012] The thermally conductive sheet according to the present invention is a thermally conductive sheet including a resin layer made of a resin composition containing an epoxy resin, a curing agent, and an inorganic filler, the inorganic filler being dispersed in the epoxy resin, The epoxy resin contains a triphenylmethane type epoxy resin represented by the following formula (1): The curing agent contains at least one of triphenylmethane type phenolic resins represented by the following formula (2) or (3).

[0013] [ka] (In formula (1), R is C n H 2n+1 where n is an integer equal to or greater than 0.

[0014] [ka] (In formula (2), R is C n H 2n+1 where n is an integer equal to or greater than 0.

[0015] [ka] (In formula (3), n is an integer between 1 and 20.) Effect of the Invention

[0016] According to the present invention, it is possible to provide a resin composition that exhibits sufficient thermal conductivity when cured, and a thermally conductive sheet having a resin layer composed of the resin composition. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a top view showing the etched stack. [Diagram 2] FIG. 4 is a cross-sectional view showing an arrangement for measuring a withstand voltage. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, one embodiment of the present invention will be described.

[0019] (Resin composition) The resin composition according to the present embodiment contains a component that will ultimately constitute a cured product, that is, the resin composition according to the present embodiment contains a polymerizable component that will become a cured resin by polymerization. The resin composition according to the present embodiment also contains an inorganic filler so that the cured product has good thermal conductivity after curing. The resin composition according to the present embodiment may contain additives that are generally used as plastic compounding chemicals, to the extent that the effects of the present invention are not impaired.

[0020] In the resin composition according to this embodiment, the content of the polymerizable component in 100 parts by mass of the cured product after curing is preferably 10 parts by mass or more and 70 parts by mass or less, and more preferably 30 parts by mass or more and 40 parts by mass or less.

[0021] The cured product obtained by curing the resin composition according to this embodiment preferably contains 10 to 60 parts by volume of inorganic filler, more preferably 30 to 60 parts by volume, and even more preferably 50 to 60 parts by volume, based on 100 parts by volume of solid content. In addition, from the viewpoint that the content ratio of the inorganic filler in the cured product is likely to be within the above-mentioned range, the resin composition according to this embodiment preferably contains 30 parts by mass or more and 90 parts by mass or less of the inorganic filler, and more preferably 60 parts by mass or more and 80 parts by mass or less, per 100 parts by mass of the polymerizable component.

[0022] Furthermore, the resin composition according to this embodiment preferably contains 0.005 parts by mass or more and 0.05 parts by mass or less, and more preferably 0.01 parts by mass or more and 0.03 parts by mass or less, of the additive relative to 100 parts by mass of the inorganic filler.

[0023] The resin composition according to the present embodiment contains an epoxy resin and a curing agent as the polymerizable component. In the present embodiment, the epoxy resin is cured together with the curing agent to become a cured resin.

[0024] The epoxy resin includes a triphenylmethane type epoxy resin represented by the following formula (1). The triphenylmethane type epoxy resin represented by the following formula (1) is a solid epoxy resin that is semi-solid at room temperature (e.g., 23±2°C). Examples of the triphenylmethane type epoxy resin represented by the following formula (1) include a triphenylmethane type epoxy resin represented by the following formula (1') and a triphenylmethane type epoxy resin represented by the following formula (1''). In this specification, the term "semi-solid" refers to a state in which deformation occurs when an external force is applied but which does not naturally flow.

[0025] [ka] (In formula (1), R is C n H 2n+1 where n is an integer equal to or greater than 0.)

[0026] [ka]

[0027] [ka]

[0028] The curing agent contains at least one of the triphenylmethane type phenolic resins represented by the following formula (2) or (3). Examples of the triphenylmethane type phenol resin represented by the following formula (2) include a triphenylmethane type phenol resin represented by the following formula (2') and a triphenylmethane type phenol resin represented by the following formula (2'').

[0029] [ka] (In formula (2), R is C n H2n+1 where n is an integer equal to or greater than 0.

[0030] [ka] (In formula (3), n is an integer between 1 and 20.)

[0031] [ka]

[0032] [ka]

[0033] The total amount of the epoxy resin and the curing agent in the polymerizable component is preferably 80% by mass or more and 100% by mass or less, and more preferably 90% by mass or more and 100% by mass or less.

[0034] The ratio of the equivalent of the epoxy resin curing agent to the equivalent of the epoxy resin (the molar ratio of the active water content of the epoxy resin curing agent to the epoxy groups of the epoxy resin) is preferably 1 / 2 or more and 2 / 1 or less, and more preferably 2 / 3 or more and 3 / 2 or less.

[0035] The inorganic filler is dispersed in the epoxy resin. Examples of the inorganic filler include inorganic particles such as boron nitride filler, aluminum nitride filler, silicon nitride filler, gallium nitride filler, alumina filler, silicon carbide filler, silicon dioxide filler, magnesium oxide filler, and diamond filler. Among these, boron nitride filler (boron nitride particles) is preferred.

[0036] The inorganic filler preferably contains aggregated particles formed by agglomeration of a plurality of primary particles. By containing the aggregated particles, the particle diameter of the inorganic particles can be increased, and therefore the interval between the inorganic particles in the epoxy resin can be reduced. This can further improve the thermal conductivity (heat dissipation) of the resin composition according to the present embodiment when it is cured.

[0037] The inorganic filler may include aluminum nitride whiskers.

[0038] Aluminum nitride whiskers are fibrous, highly thermally conductive inorganic fillers that are 2 to 3 μm in thickness and several tens to several thousand μm in length, and have a thermal conductivity of 170 W / (m·K) or higher at 20°C. Since aluminum nitride whiskers exhibit high thermal conductivity and have the above-mentioned length, it is believed that when aluminum nitride whiskers are contained in the resin composition according to the present embodiment together with the inorganic particles, they will play a role in connecting the inorganic particles together when the resin composition is cured. In other words, it is believed that a heat dissipation path connecting the inorganic particles together will be formed in the cured resin composition, and heat dissipation will be promoted via this heat dissipation path. This is believed to result in further improved thermal conductivity of the cured product of the resin composition according to this embodiment.

[0039] When the inorganic filler contains aluminum nitride whiskers, the epoxy resin preferably further contains a liquid epoxy resin that is liquid at room temperature (23±2° C.) By the epoxy resin further containing a liquid epoxy resin, the aluminum nitride whiskers can be more thoroughly dispersed in the epoxy resin.

[0040] As the liquid epoxy resin, a commercially available liquid bisphenol A type epoxy resin can be used. Examples of commercially available liquid bisphenol A type epoxy resins include JER (registered trademark) 825, JER (registered trademark) 827, JER (registered trademark) 828, JER (registered trademark) 828EL, JER (registered trademark) 828US, JER (registered trademark) 828XA, and JER (registered trademark) 824. Among these, it is preferable to use JER (registered trademark) 828.

[0041] In the resin composition of this embodiment, the liquid epoxy resin is contained in an amount of preferably 20 to 30 parts by volume per volume part of aluminum nitride whiskers, more preferably 22 to 28 parts by volume, and even more preferably 24 to 26 parts by volume.

[0042] As described above, in order to sufficiently form heat dissipation paths between the inorganic particles by the aluminum nitride whiskers, it is preferable that the aluminum nitride whiskers are in a dispersed state. On the other hand, aluminum nitride whiskers are generally aggregated in a cotton-like form. Therefore, it is preferable that the aluminum nitride whiskers are loosened and dispersed in the liquid epoxy resin.

[0043] When the inorganic filler further contains aluminum nitride whiskers, in the cured product obtained by curing the resin composition according to this embodiment, the aluminum nitride whiskers are contained in an amount of preferably 0.07 to 0.50 volume parts, more preferably 0.08 to 0.40 volume parts, and even more preferably 0.08 to 0.34 volume parts, relative to the total volume of the inorganic filler.

[0044] Incidentally, the reason why the resin composition according to the present embodiment exhibits sufficient thermal conductivity when cured is not clear, but the present inventors believe the reason to be as follows.

[0045] In general, in order for a resin composition containing a thermosetting resin to exhibit sufficient thermal conductivity when it is cured, it is necessary to generate sufficient lattice vibration in the cured product. In order to generate sufficient lattice vibration in the cured product, it is necessary to suppress scattering of phonons having thermal energy and to sufficiently propagate the phonons as wave packets. Here, the resin composition according to the present embodiment contains, as the polymerizable component, a triphenylmethane type epoxy resin having three epoxy groups in its structure that contribute to the crosslinking reaction, as represented by the above formula (1), and also contains a triphenylmethane type phenolic resin (curing agent) having three or more hydroxyl groups (active hydrogens) in its structure that contribute to the crosslinking reaction, as represented by the above formula (2) or (3). Therefore, it is considered that the crosslinking reaction proceeds such that the triphenylmethane type epoxy resin and the triphenylmethane type phenolic resin are connected to each other to form a large single molecule. Therefore, it is believed that when the resin composition according to this embodiment is cured, scattering of phonons can be suppressed, and the phonons can be sufficiently propagated as wave packets. In addition, since the resin composition according to the present embodiment contains a triphenylmethane type epoxy resin having three aromatic rings as represented by the above formula (1), and also contains a triphenylmethane type phenolic resin (curing agent) having three or more aromatic rings as represented by the above formula (2) or (3), it is believed that when the resin composition according to the present embodiment is cured, these aromatic rings form a tightly stacked structure electronically in the cured body. This also suppresses the scattering of phonons, and it is believed that the phonons can be sufficiently propagated as wave packets. Furthermore, since the resin composition according to the present embodiment contains a triphenylmethane type epoxy resin as represented by the above formula (1) and a triphenylmethane type phenol resin as represented by the above formula (2) or (3), as described above, it is considered that the density of π electrons in the resin composition is relatively high. It is believed that these π electrons also contribute to thermal conductivity, like the free electrons that form metallic bonds in metals. Therefore, it is believed that the thermal conductivity of the resin composition according to this embodiment, when cured, is also enhanced by the π electrons, which are believed to be present at a relatively high density. For the reasons described above, the present inventors believe that the resin composition according to this embodiment exhibits sufficient thermal conductivity.

[0046] Examples of the additives include a curing accelerator that accelerates the curing reaction between the epoxy resin and the curing agent, as well as a dispersant, a tackifier, an antiaging agent, an antioxidant, a processing aid, a stabilizer, an antifoaming agent, a flame retardant, a thickener, and a pigment.

[0047] Examples of the hardening accelerator include tetraphenylphosphonium tetraphenylborate, imidazoles, triphenylphosphate (TPP), amine-based hardening accelerators, etc. Examples of the amine-based hardening accelerator include boron trifluoride monoethylamine, etc.

[0048] The resin composition according to the present embodiment preferably contains 0.5 parts by mass or more and 1.5 parts by mass or less of the curing accelerator, and more preferably 0.5 parts by mass or more and 1.0 part by mass or less, per 100 parts by mass of the epoxy resin and the curing agent in total.

[0049] The resin composition according to the present embodiment may be in a state where the curing reaction has progressed to some extent but has not yet been completely cured. In other words, the resin composition may be in a state where the curing reaction has progressed in a part of the resin composition. For example, the resin composition may be coated in a sheet form in a fluid state and then partially cured. Even in a state where the curing reaction has progressed in a part, the resin composition according to the present embodiment contains the above-mentioned epoxy resin, the above-mentioned curing agent, and the above-mentioned inorganic filler.

[0050] (Method of producing resin composition) The method for producing a resin composition according to this embodiment includes a kneading step of kneading raw materials containing the triphenylmethane type epoxy resin of the above formula (1), at least one of the triphenylmethane type phenolic resins (curing agents) of the above formulas (2) and (3), and an inorganic filler, to prepare a resin composition in which the inorganic filler is dispersed in the triphenylmethane type epoxy resin of the above formula (1). The inorganic filler preferably contains boron nitride filler (boron nitride particles). The inorganic filler preferably contains aggregated particles formed by agglomerating a plurality of primary particles.

[0051] The inorganic filler may contain aluminum nitride whiskers. When the inorganic filler contains aluminum nitride whiskers, the epoxy resin preferably contains a liquid epoxy resin that is liquid at room temperature in addition to the triphenylmethane type epoxy resin of the above formula (1). Furthermore, when the inorganic filler contains aluminum nitride whiskers, in the method for producing a resin composition according to this embodiment, it is preferable to carry out a pre-kneading step of dispersing the aluminum nitride whiskers in the liquid epoxy resin prior to the kneading step.

[0052] As described above, aluminum nitride whiskers are generally aggregated in a cotton-like form, but by carrying out a preliminary kneading step before the kneading step as described above, the cotton-like aggregated aluminum nitride whiskers can be sufficiently loosened in the liquid epoxy resin. In the method for producing a resin composition according to this embodiment, the kneading step is carried out with aluminum nitride whiskers that have been sufficiently loosened in this way, so that the aluminum nitride whiskers can be sufficiently dispersed in the epoxy resin. This allows the inorganic particles dispersed in the epoxy resin to be sufficiently connected by the aluminum nitride whiskers, so that the thermal conductivity of the resin composition obtained by the above-mentioned production method when it is made into a cured product can be further improved.

[0053] As described above, when the inorganic filler contains aluminum nitride whiskers and the epoxy resin contains a liquid epoxy resin, a preliminary kneading step is performed before the kneading step, so that the kneading step can be performed in a state in which the aluminum nitride whiskers are sufficiently loosened, and therefore the inorganic particles can be sufficiently dispersed in the resin composition without excessive kneading in the kneading step. This allows the inorganic filler to be sufficiently dispersed in the epoxy resin while relatively maintaining the aggregated state of the aggregated particles even when the inorganic filler contains aggregated particles. As described above, the inclusion of aggregated particles allows the spacing between inorganic particles to be reduced, making it easier to form a heat dissipation path between inorganic particles by aluminum nitride whiskers in the resin composition. As a result, the thermal conductivity of the resin composition when it is cured can be further improved.

[0054] (Thermal Conductive Sheet) The thermally conductive sheet according to the present embodiment includes a resin layer made of the above-mentioned resin composition, and therefore has improved thermal conductivity.

[0055] The material of the adherend of the thermally conductive sheet is preferably a metal, more specifically, a metal containing copper or aluminum.

[0056] The thermally conductive sheet according to the present embodiment can be used in a metal base circuit board. The metal base circuit board is configured, for example, by bonding a circuit layer to a thermally conductive sheet. Since the metal base circuit board configured in this manner has the thermally conductive sheet according to the present embodiment, the thermal conductivity of the metal base circuit board is also improved.

[0057] Furthermore, the thermally conductive sheet according to the present embodiment is used, for example, in a power module. The power module is configured, for example, by mounting heat generating elements such as semiconductor chips and power ICs on the circuit layer of the metal base circuit board, sealing these elements once with silicone gel, and then performing resin molding on the silicone gel. Since the power module configured in this way has the thermally conductive sheet according to the present embodiment, the thermal conductivity of this power module is also improved.

[0058] The resin composition and the thermally conductive sheet according to the present invention are not limited to the above-mentioned embodiment. The resin composition and the thermally conductive sheet according to the present invention are not limited by the above-mentioned action and effect. The resin composition and the thermally conductive sheet according to the present invention can be modified in various ways without departing from the gist of the present invention. EXAMPLES

[0059] Next, the present invention will be described in more detail with reference to examples and comparative examples. Note that the following examples are intended to explain the present invention in more detail, and are not intended to limit the scope of the present invention.

[0060] Example 1 (Equivalent to Reference Example 1) ) The resin composition according to Example 1 was obtained by kneading epoxy resin A as a triphenylmethane type epoxy resin, phenol resin A (curing agent) as a triphenylmethane type phenol resin, a curing accelerator, and an inorganic filler. The epoxy resin A, the phenolic resin A, the curing accelerator, and the inorganic filler are as follows: Epoxy resin A: a triphenylmethane type epoxy resin represented by the following formula (1') (Tactix (registered trademark) 742, manufactured by Huntsman Chemical) Phenolic resin A (curing agent): Triphenylmethane type phenolic resin represented by the following formula (2') (Tris P-PHBA, manufactured by Honshu Chemical Co., Ltd.) Curing accelerator: Tetraphenylphosphonium tetraphenylborate (TPP-K (registered trademark), manufactured by Hokko Chemical Industry Co., Ltd.) · Inorganic filler: Boron nitride filler (BN filler) The epoxy resin A and the phenolic resin A were contained in the resin composition at an equivalent ratio of 1:1. The curing accelerator was contained in the resin composition in an amount of 0.01 part by mass per 100 parts by mass of the total of the epoxy resin A and the phenol resin A. Furthermore, an inorganic filler was contained in the resin composition so that the content of the inorganic filler was 59.0 parts by volume when the solid content of the cured product of the resin composition after curing was taken as 100 parts by volume.

[0061] [ka]

[0062] [ka]

[0063] Example 2 A resin composition according to Example 2 was obtained in the same manner as in Example 1, except that phenolic resin B (curing agent) was used instead of phenolic resin A as a triphenylmethane type phenolic resin. As the phenol resin B, a triphenylmethane type phenol resin represented by the following formula (2″) (BIP-PHAP, manufactured by Asahi Organic Chemicals Co., Ltd.) was used.

[0064] [ka]

[0065] ( reference Example 3) The same procedure as in Example 1 was repeated, except that phenolic resin C (curing agent) was used as a triphenylmethane type phenolic resin instead of phenolic resin A. reference A resin composition according to Example 3 was obtained. As the phenol resin C, a triphenylmethane type phenol resin represented by the following formula (3) (TPM-100, manufactured by Gun-ei Chemical Industry Co., Ltd.) was used.

[0066] [ka] (In formula (3), n is an integer between 1 and 20.)

[0067] Example 4 A resin composition according to Example 4 was obtained in the same manner as in Example 1, except that epoxy resin B, which is a triphenylmethane type epoxy resin, was used instead of epoxy resin A. As the epoxy resin B, a triphenylmethane type epoxy resin represented by the following formula (1″) (EPALLOY (registered trademark) 9000, manufactured by CVC Thermoset C) was used.

[0068] [ka]

[0069] Example 5 A resin composition according to Example 5 was obtained in the same manner as in Example 1, except that epoxy resin B was used instead of epoxy resin A and phenolic resin B was used instead of phenolic resin A.

[0070] ( reference Example 6) The same procedure as in Example 1 was repeated, except that epoxy resin B was used instead of epoxy resin A and phenolic resin C was used instead of phenolic resin A. reference A resin composition according to Example 6 was obtained.

[0071] Comparative Example 1 A resin composition according to Comparative Example 1 was obtained in the same manner as in Example 1, except that a novolac-type phenolic resin (phenolic resin D) was used instead of phenolic resin A.

[0072] Comparative Example 2 A resin composition according to Comparative Example 2 was obtained in the same manner as in Example 1, except that epoxy resin B was used instead of epoxy resin A and that novolac-type phenolic resin was used instead of phenolic resin A.

[0073] Comparative Example 3 A resin composition according to Comparative Example 3 was obtained in the same manner as in Example 1, except that a polyfunctional epoxy resin other than a triphenylmethane type epoxy resin was used instead of the epoxy resin A, and a phenolic resin represented by the following formula (4) (phenolic resin E, GS-200, manufactured by Gun-ei Chemical Industry Co., Ltd.) was used instead of the phenolic resin A.

[0074] [ka]

[0075] Comparative Example 4 A resin composition according to Comparative Example 4 was obtained in the same manner as in Example 1, except that a bisphenol A type epoxy resin (JER (registered trademark) 1009, manufactured by Mitsubishi Chemical Holdings Corporation) was used instead of the epoxy resin A, and a novolac type phenolic resin (phenolic resin D) was used instead of the phenolic resin A.

[0076] <Thermal conductivity> For the measurement of thermal conductivity, an insulating and heat-dissipating sheet was prepared as follows. First, the base material, copper foil (area: 2500 cm 2 ) was coated with the resin composition according to each example (thickness: about 200 μm). The coating method was a roll-to-roll coater method, and the drying conditions were 120° C. and 5 minutes. In this manner, a resin sheet was produced for each of the resin compositions according to each example. Next, for each of the resin sheets according to each example, two of the same type of resin sheets were stacked together with the surfaces not in contact with the substrate facing each other, and then heat pressed at a temperature of 100°C, a pressure of 8 MPa, and a time of 20 minutes to produce an insulating heat dissipation sheet with metal foil (insulating layer thickness 0.22±0.04 mm).

[0077] The copper foil, which was the metal foil, was removed from both sides of the insulating heat dissipation sheet by etching, and a rectangular resin cured body was cut out from this insulating heat dissipation sheet with each side measuring 10 mm ± 0.5 mm. An anti-reflective agent (manufactured by Fine Chemical Japan Co., Ltd., product number: FC-153) was applied to both sides of the cut-out cured resin body to prepare a sample for measuring thermal diffusivity. The thermal conductivity value was calculated by multiplying the thermal diffusivity value measured for the thermal diffusivity measurement sample using a xenon flash analyzer (NETZSCH, LFA-447 type) by the specific heat value measured by heat flux DSC in accordance with JIS 7123:1987, and the density value measured by the immersion method in accordance with JIS K 7122:1999. The thermal diffusivity value was calculated by arithmetic averaging the thermal diffusivity values ​​measured for three measurement samples. In addition, the thermal diffusivity was measured at five points for each measurement sample, and the arithmetic average of the three values ​​excluding the maximum and minimum values ​​for each measurement sample was used as the measured value. The results of measuring the thermal conductivity are shown in Table 1 below.

[0078] <Peel strength> The resin composition according to each of the above examples was applied to one side of an electrolytic copper foil (thickness: 35 μm) to prepare two sheets having a resin layer (thickness: 145 μm). Next, the two sheets were hot-pressed (3.0 MPa, 120°C, 20 min) to bond the resin layers together, and one copper foil was peeled off from the back surface of the sheet. An aluminum plate was then placed on the surface from which the copper foil had been peeled off, and the sheet was transferred to the aluminum plate by hot pressing (2.0 MPa, 120°C, 20 min), and the copper foil was then peeled off from the sheet to obtain a semi-cured sheet. Next, the adherend (1 oz copper foil) was laminated onto this semi-cured sheet, and the resin layer and adherend were integrated by heat pressing (2.0 MPa, 180°C, 120 min). After the resin layer was sufficiently cured, it was cut into a size of 20 mm x 100 mm, and the cut-out adherend was processed (etched) to a width of 10 mm to prepare a test piece for the peel test. The test pieces were subjected to a 90° peel test at a peeling speed of 50 mm / min, and the adhesive strength between the adherend and the resin layer was evaluated based on the peel strength. The peel strength was measured and the results are shown in Table 1 below.

[0079] <Dielectric breakdown strength (BDV)> The dielectric breakdown strength was measured using a dielectric breakdown device that has a crest factor between 1.34 and 1.48, can apply a voltage at a frequency of 50 or 60 Hz, and has a maximum voltage of AC 10 kV (effective value). Details of the measurement method will be described with reference to Figs. 1 and 2. The copper foil on one side of a thermally conductive sheet measuring 75±1 mm×65±1 mm was peeled off to obtain a resin sheet, and an aluminum plate was laminated on the surface of the resin sheet from which the copper foil 13 had been peeled off, followed by heating to obtain a laminated sheet in which the aluminum plate was integrated with the resin sheet. Next, the laminated sheet was further heated to completely harden the resin sheet, thereby obtaining a dielectric breakdown strength measurement sample 14 shown in FIG. 1. The resin sheet was produced using the resin composition according to each example. 2, the dielectric breakdown strength measurement sample 14 was placed on a brass disk electrode 17 (Φ: 40 mm) with the aluminum plate side facing down in insulating oil 16 (JIS C2320:1999) in an oil tank 15, and a brass spherical electrode 18 (Φ: 15 mm, weight: 50 g) was placed on top of the dielectric breakdown strength measurement sample 14 so as to contact the approximate center of the dielectric breakdown strength measurement sample 14. The insulating oil 16 was kept at 20±10°C, and a voltage was continuously applied to the dielectric breakdown strength measurement sample 14 at a voltage increase rate of 1 kV (effective value) / sec until dielectric breakdown occurred. As a criterion for determining dielectric breakdown, a cutoff current was set to 25 mA. The voltage (unit: kV) at which dielectric breakdown occurred was divided by the thickness (unit: mm) of the dielectric breakdown strength measurement sample 14 to determine the dielectric breakdown strength. The results of measuring the dielectric breakdown strength (BDV) are shown in Table 1 below.

[0080] <Dielectric strength> The withstand voltage was measured using a dielectric breakdown device that has a crest factor between 1.34 and 1.48, can apply a voltage at a frequency of 50 or 60 Hz, and has a maximum voltage of AC 10 kV (effective value). Details of the measurement method will be described with reference to Figs. 1 and 2. The copper foil 13 on one side of the insulating heat dissipation sheet of 75±1 mm×65±1 mm was peeled off, and an aluminum plate was laminated on the peeled surface and heated to integrate the aluminum plate with the insulating heat dissipation sheet, and further heated to completely harden the laminate, thereby obtaining the voltage resistance measurement sample 14 shown in FIG. 1. The insulating heat dissipation sheet was prepared with the resin composition according to each example. As shown in FIG. 2, the voltage resistance measurement sample 14 was placed on a brass disk electrode 17 (Φ: 40 mm) with the aluminum plate side facing down in insulating oil 16 (JIS C2320:1999) in an oil tank 15, and a brass spherical electrode 18 (Φ: 15 mm, weight: 50 g) was placed on the voltage resistance measurement sample 14 so as to contact the approximately center part of the voltage resistance measurement sample 14. The insulating oil 16 was kept at 20±10° C., and AC 3.0 kV (effective value) was applied to the voltage resistance measurement sample 14 for 1 minute. If no dielectric breakdown occurred, the voltage was immediately increased to AC 0.5 kV (effective value) and applied for 1 minute, and then increased in 0.5 kV (effective value) intervals (0.5 kV (effective value) steps, applied for 1 minute) until dielectric breakdown occurred. As a criterion for determining whether dielectric breakdown occurred, a cutoff current was set to 10 mA. The withstand voltage was calculated by dividing the applied voltage, which was 0.5 kV (effective value) lower than the voltage at which dielectric breakdown occurred, by the thickness (unit: mm) of the withstand voltage measurement sample 14. The withstand voltage of each example was measured and the results are shown in Table 1 below. In addition, the glass transition temperature Tg is also listed in Table 1 below, and this glass transition temperature Tg means the midpoint glass transition temperature according to JIS K7121:2012.

[0081] [Table 1]

[0082] <Thermal conductivity> As shown in Table 1, it can be seen that the thermal conductivity of the cured product is significantly improved in the resin compositions of each Example compared to the resin compositions of each Comparative Example, i.e., the thermal conductivity is significantly improved. In particular, it can be seen that when epoxy resin B (triphenylmethane type epoxy resin represented by the above formula (1'')) is used, the thermal conductivity is further improved. This shows that the thermal conductivity of the cured product obtained by using a resin composition containing a specific multifunctional epoxy resin (a triphenylmethane-type epoxy resin represented by the above formula (1)) and a specific multifunctional phenolic resin (at least one of the triphenylmethane-type phenolic resins represented by the above formulas (2) and (3)) can be significantly improved.

[0083] <Peel strength> Furthermore, as shown in Table 1, it can be seen that the resin compositions using epoxy resin A (triphenylmethane type epoxy resin represented by the above formula (1')) or epoxy resin B as the epoxy resin (the resin compositions of each Example and the resin compositions of Comparative Examples 1 and 2) have significantly improved peel strength compared to the resin compositions not using epoxy resin A or epoxy resin B (the resin compositions of Comparative Examples 3 and 4). In particular, it is apparent that the resin compositions according to each of the examples other than the resin composition according to Example 2 (a resin composition containing epoxy resin A and phenol resin B) have significantly improved peel strength. This shows that the peel strength can be significantly improved by using a specific multifunctional epoxy resin as the epoxy resin.

[0084] <Dielectric breakdown strength (BDV) and withstand voltage> Furthermore, as shown in Table 1, the resin compositions according to each Example exhibited values ​​for at least one of the dielectric breakdown strength (BDV) or the voltage resistance that were equivalent to or greater than those of the resin compositions according to each Comparative Example. This shows that even when a resin composition containing a specific multifunctional epoxy resin (a triphenylmethane-type epoxy resin represented by the above formula (1)) and a specific multifunctional phenol resin (at least one of the triphenylmethane-type phenol resins represented by the above formulas (2) and (3)) is used, at least one of the dielectric breakdown strength (BDV) and the withstand voltage exhibits a relatively high value. [Explanation of symbols]

[0085] 13 copper foil, 14 measurement samples (dielectric breakdown strength measurement sample, voltage endurance measurement sample), 15 oil tank, 16 insulating oil, 17 brass disk electrode, 18 brass spherical electrode.

Claims

1. A thermally conductive sheet including a resin layer made of a resin composition containing an epoxy resin, a curing agent, and an inorganic filler, the inorganic filler being dispersed in the epoxy resin, The resin composition comprises The epoxy resin includes a triphenylmethane type epoxy resin represented by the following formula (1) and a triphenylmethane type phenol resin represented by the following formula (2″) as the curing agent, or The epoxy resin includes a triphenylmethane type epoxy resin represented by the following formula (1″) and the curing agent includes a triphenylmethane type phenol resin represented by the following formula (2′), The thermally conductive sheet is used by adhering the resin layer to a circuit layer of a metal base circuit board. 【Chemistry 1】 (In the formula (1), R is H or CH 3 (represented by 【Chemistry 2】

2. The inorganic filler includes boron nitride particles. The thermally conductive sheet according to claim 1 .

3. The resin composition comprises: The epoxy resin includes a triphenylmethane type epoxy resin represented by the following formula (1″) and the curing agent includes a triphenylmethane type phenol resin represented by the following formula (2″). The thermally conductive sheet according to claim 1 or 2. 【Chemistry 3】

Citation Information

Patent Citations

  • Heat-resistant epoxy resin composition

    JP1983198526A

  • Epoxy resin molding material for sealing semiconductor

    JP1989249826A

  • Epoxy resin composition for semiconductor sealing and semiconductor device

    JP1999147936A

  • Epoxy resin composition for sealing and semiconductor devices

    JP2001181479A

  • Resin composition for optical semiconductor device and optical semiconductor device

    JP2002097252A